Relationship between Primary Tumors of Nasopharyngeal Carcinoma with the Degree of Conductive Hearing Loss in Dr. Mohammad Hoesin Hospital Palembang - Denny Satria Utama; Eriza; Priscilla Ralahayu; Erial Bahar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Nasopharyngeal carcinoma is a malignant tumor that grows in the nasopharyngeal area with predilection in the fossa Rossenmuller and the nasopharyngeal roof adjacent to the Eustachian tube, so one of NPC’s early symptoms is ear symptoms. Hearing loss is a common symptom found in people with NPC due to dysfunction of the Eustachian tube, a continuing middle ear disorder that can result in conductive hearing loss.This study aims to find out the relationship between primary tumor of NPC and the degree of conductive hearing loss at dr. Mohammad Hoesin Hospital Palembang. Methods. This is a cross sectional study that obtained 42 samples from the medical records at Dr. Mohammad Hoesin Hospital Palembang that met the inclusion and exclusion criteria. The study subjects collected in total sampling have been conducted audiometry examinations at the ORLHNS clinic of Dr. Mohammad Hoesin Hospital Palembang during the period January 2019 - April 2021. Results. The proportion of hearing loss in NPC patients in this study was 30 subjects (71.4%) with the highest proportion of hearing loss complaints being 33.3%. The proportion of conductive hearing loss of nasopharyngeal carcinoma patients in the study was 33 subjects (78.5%) right ear and 28 subjects (66.7%) left ear. There was a significant association between the degree of the NPC primary tumor and the incidence of conductive deafness of the left ear, but there was no significant association in the right ear. There is a significant correlation between NPC primary tumors and left ear hearing thresholds at frequencies of 500 Hz and 4000 Hz, but there is no significant association between the degree of NPC primary tumor and right ear hearing loss. Conclusions. There is significant correlation between the primary tumor of NPC and the hearing threshold of the left ear but there was no significant association in the right ear.